Analisis Penggunaan Fire Alarm System di Bandara Internasional Jawa Barat Kertajati - Reva Herlambang; Lela Nurpulaela (Peneliti.net, 2023)
Fire in the workplace can have consequences that are detrimental to many parties, including the business world, customers, workforce, authorities and the whole community. As a result of fires in the workplace can cause casualties, material losses, work losses and other indirect losses, especially if the fire starts at an essential object, it can have an even wider impact. fire alarm PT. BIJB works with a semi-addressable concept, where the installed detectors are smoke and temperature sensors using a conventional system, while the control panel uses an addressable system. Fire alarm is used for early detection of fire. The main components of the fire alarm system PT. The BIJB includes a control panel, zone module, manual alarm button, smoke detector and temperature sensor.